2017
DOI: 10.4007/annals.2017.185.1.2
|View full text |Cite
|
Sign up to set email alerts
|

New $\mathrm{G}_2$-holonomy cones and exotic nearly Kähler structures on $S^6$ and $S^3 \times S^3$

Abstract: Abstract. There is a rich theory of so-called (strict) nearly Kähler manifolds, almostHermitian manifolds generalising the famous almost complex structure on the 6-sphere induced by octonionic multiplication. Nearly Kähler 6-manifolds play a distinguished role both in the general structure theory and also because of their connection with singular spaces with holonomy group the compact exceptional Lie group G2: the metric cone over a Riemannian 6-manifold M has holonomy contained in G2 if and only if M is a nea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(117 citation statements)
references
References 43 publications
0
113
0
4
Order By: Relevance
“…Four of these are homogeneous and were known since 1968 [23]: the round 6-sphere endowed with the non-integrable almost complex structure induced by octonionic multiplication on R 7 Im O and the 3-symmetric spaces CP 3 = Sp(2)/U (1) × Sp (1), S 3 × S 3 = SU (2) 3 /SU (2) and F 3 = SU (3)/T 2 . Recently two inhomogeneous nearly Kähler structures on S 6 and S 3 × S 3 were found in [9]. Finite quotients of the homogeneous nearly Kähler manifolds have also been studied [8].…”
Section: Introductionmentioning
confidence: 99%
“…Four of these are homogeneous and were known since 1968 [23]: the round 6-sphere endowed with the non-integrable almost complex structure induced by octonionic multiplication on R 7 Im O and the 3-symmetric spaces CP 3 = Sp(2)/U (1) × Sp (1), S 3 × S 3 = SU (2) 3 /SU (2) and F 3 = SU (3)/T 2 . Recently two inhomogeneous nearly Kähler structures on S 6 and S 3 × S 3 were found in [9]. Finite quotients of the homogeneous nearly Kähler manifolds have also been studied [8].…”
Section: Introductionmentioning
confidence: 99%
“…B. Butruille showed that the only homogeneous 6-dimensional NK manifolds are the NK 6-sphere 6 , the NK 3 × 3 , the complex projective space 3 and the flag manifold (3)∕ (1) × (1). It is worth mentioning that L. Foscolo and M. Haskins [17] remarkably constructed inhomogeneous NK structures on both manifolds of 6 and 3 × 3 . In order to avoid confusion, from now on of this paper, when we say NK 6 or NK 3 × 3 , we mean always the homogeneous NK 6 or the homogeneous NK 3 × 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recall from Proposition 6 that A takes the form in (4.8), determined by functions f ± , g ± : R ≥0 → R. The next result gives the conditions on f ± , g ± so that such A extends over a singular orbit at t = 0. To state it, we observe that Lemma 8 in Appendix A shows that for any SU(2) 2 × U (1)-invariant G 2 -metric which smoothly extends over a singular orbit at t = 0 must be of the form (2.13) for functions A 1 , A 2 = A 3 , B 1 , B 2 = B 3 which admit Taylor expansions of the form 13) for some b ∈ R\{0} and real analytic even functions …”
Section: Initial Conditionsmentioning
confidence: 99%
“…The compatible metric determined by this SU(3) structure on {t} × M is [19] 13) and the resulting metric on R t × M, compatible with the G 2 -structure ϕ = dt ∧ω+ 1 , is given by g = dt 2 + g t . Recall also that this metric has holonomy in G 2 if and only if the SU(3)-structure above solves the Hitchin flow equations (2.2).…”
Section: Su(2) 2 -Invariant G 2 -Manifolds Of Cohomogeneity-1mentioning
confidence: 99%
See 1 more Smart Citation